Role of key players in paradigm shifts of prostate cancer bone metastasis - Sohail A (Cancer Management and Research, 2018)
Ayesha Sohail,1 Lubna Sherin,2 Saad I Butt,1 Sana Javed,1 Zhiwu Li,3,4 Sohail Iqbal,5 O Anwar Be’g6 1Department of Mathematics, Comsats Institute of Information Technology, Lahore, Pakistan; 2Department of Chemistry, Comsats Institute of Information Technology, Lahore Pakistan; 3Institute of Systems Engineering, Macau University of Science and Technology, Taipa, Macau; 4School of Electro-Mechanical Engineering, Xidian University, Xi’an, China; 5Department of Medicine, Sir Ganga Ram Hospital, Fatima Jinnah Medical College, Lahore, Pakistan; 6Fluid Mechanics, Spray Research Group, Mechanical and Petroleum Engineering, School of Computing, Science and Engineering, University of Salford, Manchester, UK Abstract: The decreased bone mineral density and compromised bone strength predispose individuals to skeletal osteoporosis. Both prostate cancer and bone metastasis caused by cancer invasion have remained a great challenge to researchers. With the advancement in the fields of biochemistry and biomechanics, the molecular mechanisms that make prostate cancer metastasize to bone have recently been identified, and they provide new molecular targets for drug development. Many biochemical by-products have been identified to help in understanding the interaction between the bone and the tumor. Enhanced clinical management of patients with bone metastases was reported during the past decade; however, the anticipated risk and the response to the therapy are still challenging to assess. In this review, the key players that play a dominant role in secondary osteoporosis are addressed. An attempt is made to provide the readers with a clear understanding of the communication pathways between each of the cell types involved in this vicious cycle. Furthermore, the role of Wnts, sclerostin, RANKL, PTHrP, and their respective clinical studies are addressed in this study. Keywords: prostate cancer metastatic bone disease (PCa MBD), vicious cycle, macrophages, Wnts signaling